Non-IgE-mediated food allergy during infancy. Issue 3 (June 2020) - Devonshire, Ashley L.; Durrani, Sandy; Assa'ad, Amal
Abstract : Purpose of review: Is to highlight the recent advances in the diagnosis and management of non-IgE-mediated food allergy which is a common consideration in primary care and in allergy and gastroenterology subspecialty practices evaluating infants. Recent findings: The review focuses on food protein-induced enterocolitis syndrome (FPIES) and includes other non-IgE-mediated food allergy in nursing infants, food protein-induced allergic proctocolitis, and food protein-induced enteropathy. For FPIES, we review the 2017 International Consensus Guidelines that provided the first comprehensive framework for its diagnosis and management and that were supplemented by a 2019 position paper by the European Academy of Allergy and Clinical Immunology. We review recent reports that support FPIES as a diagnosis of primarily infants, highlight the problem of delayed diagnosis, reveal the need for improved biomarkers, emphasize new and common food protein triggers, and identify new approaches for evaluation of tolerance. Summary: As formal diagnostic criteria for non-IgE-mediated food allergies are defined and prevalence data is increasingly reported, there will likely be improved recognition and evaluation of these conditions. Currently, large-scale prospective studies evaluating their incidence and prevalence, associated risk factors, and natural history are needed. Although avoidance of the suspected trigger food protein remains the cornerstone of management, additional studies of underlying pathophysiology and biomarkers of disease will likely reveal new avenues for therapeutics.